Effects of the North Eastern (Esan) Thai Folk Dance Exercise Program on Physical Fitness and Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus - phinyo, kittiphoom; Phinyo, Piyanuch; Aphiphatkan, Wachirasak; Pangsuk, Pavinee; Niyomsat, Yapat; janhauna, Saisuda; Mahem, Khannistha (Journal of Research in Nursing-Midwifery and Health Sciences, 2020)
This research aims to compare the effects of the Northeastern (Esan) Thai folk dance exercise program on physical fitness and blood sugar levels in patients with type 2 diabetes mellitus before and after the implementation of the exercise program. It was one-group pretest-posttest design research. The samples were 15 patients diagnosed with type 2 diabetes mellitus without hypertension with the duration of treatment for more than 5 years and unable to control blood sugar levels and willing to participate in the research project. The samples were selected by a purposive sampling method. The samples attended the Northeastern (Esan) Thai folk dance exercise program 3 times a week, 50 minutes each time for 12 weeks. The instruments used to collect data were blood sugar level record and physical fitness record. The data were analyzed by paired t-test. The results indicated that the blood sugar levels of the samples who attended the Northeastern (Esan) Thai folk dance exercise program were significantly lower than before attending the program (p < .05). Lung capacity, trunk forward flexion, balance and physical strength were also greater than those of before attending the exercise program with statistical significance (p <.05). The recommendations for future research are as follows. The effectiveness of the Northeastern (Esan) Thai folk dance exercise program in patients with type 2 diabetes mellitus who cannot control blood sugar levels should be studied by using two-group pretestposttest design to confirm the effectiveness of the program.